2011
DOI: 10.1111/j.1600-0463.2011.02809.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of whole‐cell protein profile analysis by SDS‐PAGE as an accurate tool to identify species and subspecies of coagulase‐negative staphylococci

Abstract: We used sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) as a tool to characterize coagulase-negative staphylococci (CoNS). Of 253 clinical isolates and 10 control strains, five species and four subspecies were analyzed. All the isolates were identified using conventional phenotypic tests and SDS-PAGE. Discrepant results between these methods, as well as less common species and subspecies, were confirmed by sodA and 16S rDNA gene sequencing. Intraspecies similarities, calculated by the Dice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…A significant amount of literature already exists discussing the uses of SDS-PAGE within the medical arena. For example, use of the technique to identify pathogenic bacteria to species is discussed by Emerson et al 25 and Kersters et al, 26 and its potential use as a screening tool to detect human bacterial pathogens is discussed by Santos et al 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant amount of literature already exists discussing the uses of SDS-PAGE within the medical arena. For example, use of the technique to identify pathogenic bacteria to species is discussed by Emerson et al 25 and Kersters et al, 26 and its potential use as a screening tool to detect human bacterial pathogens is discussed by Santos et al 27…”
Section: Discussionmentioning
confidence: 99%
“…For example, use of the technique to identify pathogenic bacteria to species is discussed by Emerson et al . and Kersters et al ., and its potential use as a screening tool to detect human bacterial pathogens is discussed by Santos et al …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number 49 strain was very close to reference strain in both dendrograms. Similar studies have shown that the whole-cell and extracellular protein profiles can be useful in the characterization and the discrimination of S. aureus strains isolated from various sources [10,[22][23][24][25][26]. Previous studies proposed that whole-cell and extracellular protein profiles were sufficient for the differentiation at species level, but the differences were inadequate at the strain level [10,12].…”
Section: Resultsmentioning
confidence: 89%
“…SDS-PAGE method has a discriminatory resolution to the level of species and subspecies (Vandamme et al 1996). Finger printing of total protein using SDS-PAGE has been applied to differentiate strains of Xanthomonas (Vandamme et al 1996;Vauterin et al 1993), members of the genus Bacillus (Berber 2004;Berber & Yenidunya 2005), members of Staphylococci (Santos et al 2012), and the group of Lactic Acid Bacteria (Ghazi et al 2009;Hong et al 2014).…”
Section: Identification Of the Amylolytic Bacteria Producing Of Phb Bmentioning
confidence: 99%
“…High resolution polyacrylamide gel electrophoresis (PAGE) of proteins with computerized analysis of profiles provided an effective approach to the investigation of taxonomic relationships among many bacterial species (Berber 2004;Berber & Yenidunya 2005). Several investigators have used SDS-PAGE of soluble bacterial polypeptides data for numerical taxonomy and an effective approach to the investigation of taxonomic relationships among many bacterial species (Berber 2004;Berber & Yenidunya 2005;Ghazi et al 2009;Santos et al 2012;Sarkono et al 2016). Therefore, this study aimed to identify the three isolates of bacterial producing bioplastics from Southeast Sulawesi, Indonesia by polyphasic taxonomy approach, particularly based on the characters of phenotypic, whole cell protein profile and genotypic characters, so as to illustrate the similarities between bacterial and the identity of the local bacterial isolates can be unveiled.…”
Section: Introductionmentioning
confidence: 99%